2016
DOI: 10.4103/0972-0707.186450
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Gutta-percha in contact with various concentrations of zinc oxide-eugenol sealer: A three-dimensional volumetric study using spiral computed tomography

Abstract: Aim:The purpose of this study was to evaluate the three-dimensional expansion of Gutta-percha (GP), at various powder/liquid ratios, of a zinc oxide-eugenol (ZOE)-based sealer using spiral computed tomography (SCT).Materials and Methods:Thirty-five freshly extracted human mandibular premolars were selected for this study. Cleaning and shaping were performed in all the teeth initially with hand K-files up to #25 and finally with RaCe rotary instruments (25/06). Teeth were randomly divided into five groups of 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Our study recorded the highest push-out bond strength when calcium hydroxide was used as an intracanal medicament [ 13 ]. Other researchers had similar findings and stated that calcium hydroxide Ca(OH) 2 used as a treatment for 14 days showed satisfying effects on the bond strength of AH Plus to root dentin [ 14 18 ]. However, according to Amin et al , intracanal treatment with Ca(OH) 2 for a week showed no changes in the bond strength of AH Plus.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our study recorded the highest push-out bond strength when calcium hydroxide was used as an intracanal medicament [ 13 ]. Other researchers had similar findings and stated that calcium hydroxide Ca(OH) 2 used as a treatment for 14 days showed satisfying effects on the bond strength of AH Plus to root dentin [ 14 18 ]. However, according to Amin et al , intracanal treatment with Ca(OH) 2 for a week showed no changes in the bond strength of AH Plus.…”
Section: Discussionmentioning
confidence: 82%
“…The reasons for the higher push-out bond strength of AH Plus might be due to a covalent linkage between an open epoxide ring and exposed amino groups in collagen protein, lower shrinkage while setting, long-term dimensional stability, and inherent volumetric expansion of AH Plus. These factors may contribute to a better AH Plus sealer bond strength [ 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Gutta-core carrier appeared to offer better micromechanical retention than the ThermaFil carrier, since the gutta-core carrier is crosslinked gutta-percha [15,16] and so it is unlikely that any chemical interaction would develop between this and the alpha-phase gutta-percha of the coating so that avoid stripping of gutta-percha from the carrier during the insertion into the root canal space. This would result in reducing voids and adequate filling of the root canal space [15] . These findings were in agreement with other studies [16,18,19] which reported that gutta-core demonstrated significantly higher bond strength than ThermaFil.…”
Section: Discussionmentioning
confidence: 99%
“…Once the fit was verified, then the root canals of each subgroup were coated with a thin layer of Endofill sealer (Dentsply Maillefer, Brazil) with paper point and obturated with gutta-core. Subgroup B: Specimens were obturated with ThermaFil (Dentsply, Maillefer, USA), with a size 40 or 45 ThermaFil obturator using the same technique as in subgroup A, but the obturator was heated to 30 seconds in Therma-prep oven [15,16] .…”
Section: Methodsmentioning
confidence: 99%
“…According to them, the major limitation of this method was to differentiate the gutta‐percha from the sealer. A few other studies were published using this same tool to compare other techniques and materials (Anbu et al, 2010; Bhatt & Rajkumar, 2015; Jain & Ballal, 2019; Jindal et al, 2017; Kandaswamy et al, 2009) and to measure the expansion of gutta‐percha in contact with various concentrations of zinc oxide‐eugenol sealer (Chandrasekhar et al, 2011; Tilakchand et al, 2016). In general, voids were identified in all specimens and thermoplasticized gutta‐percha techniques resulted in better filling than cold techniques.…”
Section: Testing Samples For Experimental Studies On Root Canal Fillingmentioning
confidence: 99%